Pengaruh Penambahan Styrofoam pada Campuran AC-WC Menggunakan Batu Sungai Pattunuang Maros - Sukur Dian Permasi; Alpius; Louise Elizabeth Radjawane (Program Studi Teknik Sipil UKI Paulus-Makassar, 2022)
This study focuses on knowing how the effect of adding Styrofoam as an additive added to the AC-WC mixture using Pattunuang River Stone, Maros Regency as a material, the research method used is a series of conventional Marshall tests, the results of the research with the plan to add variations in Styrofoam content 0%, 1 %, 2%, 3%, 4% with a composition of 36.90% coarse aggregate, 50% 30 fine aggregate, 5.8% filler, with varying levels of asphalt used 5.5% so as to obtain the characteristics of the AC-WC mixture in the test Conventional marshall obtained Stability, flow, VIM, VMA and VFB meet the 2018 Bina Marga Specifications.